Implementation of CSR concept in manufacturing SMEs = Zastosowanie koncepcji CSR w małych i średnich przedsiębiorstwach produkcyjnych - Szczanowicz, Justyna; Saniuk, Sebastian (Zielona Góra: Faculty of Economics and Management Press)
This article constitutes an attempt to propose a concept model for the implementation of Corporate Social Responsibility in small and medium-sized manufacturing enterprises. Poor CSR awareness and implementation across the SME sector is presented and discussed on the basis of research carried out by Polish Agency for Enterprise Development.
Keywords: model CSR; produkcyjne MSP; wdrożenia CSR; CSR model; manufacturing SMEs; implementation